Analytical and Theoretical Studies of Some Diazo Dyes - Hanan M. Ali (Journal of Global Pharma Technology, 2016)
Analytical studies were carried on diazo dyes that characterized 4,6-bis((E)-(3-nitrophenyl)diazenyl) benzene-1,3-diol (1), 4-((E)-(3-nitrophenyl)diazenyl)-6-((E)-(4-nitro phenyl)diazenyl)benzene -1,3-diol (2), 4-((E)-(2-nitrophenyl) diazenyl)-6-((E)-(3-nitro phenyl)diazenyl)benzene-1,3-diol (3) and 4,6-bis((E)-(2-nitrophenyl) diazenyl)benzene-1,3-diol (4). The results of the solvents effects and the pH effects were showed high solubility of these dyes in ethanol and the suitable pH values were found to be in the pH 12. Three isopiestic points were gained in the results of the azo dyes (2), (3) and (4). Add to which, the ionization (pKa) and the protonation (pKb) constants were calculated by using the half height method. The results were showed that the pKa1 values were absence intheresults ofdiazo dyes (3) and (4). Theoretical studies also approved the structures of diazo dyes (1), (2), (3) and (4). These studies were focused in the relation between the structure and the properties of these molecules. Due to the internal coordinate mechanics (ICM), the conformational analysis, the molecular mechanics (MM2) and the optimal minimization were attended for each azo dye.Keywords: Azo dyes, Internal coordinates, Conformational analysis, Molecular mechanics, Ionization constant and Protonation constant.